Retweet, yuk : setiap masalah selalu ada solusinya, kok / Intan Daswan ; editor, Aya Sophia ; ilustrasi, Triastanto S - INTAN DASWAN; Aya Sophia; Triastanto S (Diva Press, 2014)
224 hlm.: ilus.; 19 cm